Analisis Kondisi Fisik Atlet Pelatda Provinsi Jambi: Korelasi antara Parameter Fisik dan Prestasi Olahraga - Prameswari, Indah Putri; Saputra, Endarman; Murniati, Sri (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This research aims to analyze the physical condition of Jambi Province's training center athletes and its relationship with sports achievement. A total of 217 athletes who were members of the Aceh-Sumut 2024 National Sports Week training center were used as research samples. The research method used a correlational quantitative approach with instruments in the form of a series of physical condition tests. The results showed that the physical condition of Jambi Province's training center athletes was generally in the "Good" category with an average value of 21.92. Athletes' achievements at the Aceh-Sumut 2024 National Sports Week showed 6 people (2.76%) won 1st place, 18 people (8.29%) 2nd place, 27 people (12.44%) 3rd place, and 166 people (76.49%) 4th place and below. Spearman correlation test results showed a very weak but significant negative relationship (r = -0.136, p = 0.046) between physical condition and athlete achievement. In conclusion, physical condition is not the main factor determining the achievement of Jambi Province's training center athletes; rather, there are other factors that may be more dominant, such as tactical intelligence, mental readiness, and competitive experience.